2021
DOI: 10.1007/s11357-021-00397-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic prevention of COVID-19 in elderly: a case–control study

Abstract: including antihypertensive drugs, antipsychotics, antibiotics, nonsteroidal anti-inflammatory drugs, proton pump inhibitors (PPIs), oral antidiabetics (OADs), corticosteroids, immunosuppressants), comorbidities, symptoms, laboratory values, and clinical outcome were all collected. COVID-pos patients more frequently had a history of diabetes (P = .016) and alcoholism (P = .023), a lower leukocyte count (P = .014) and a higher mortality rate -29.2% versus 14.4% -(P = .014) when compared to COVID-neg patients. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…two-fold increased in the odds of dying from COVID-19, which is in line with the results published by previous studies on the main risk factors of COVID-19 mortality[2] [15]. We found no association between COVID-19 mortality and BMI, sex, hypertension, renal failure, and cancer.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…two-fold increased in the odds of dying from COVID-19, which is in line with the results published by previous studies on the main risk factors of COVID-19 mortality[2] [15]. We found no association between COVID-19 mortality and BMI, sex, hypertension, renal failure, and cancer.…”
supporting
confidence: 92%
“…Multiple organ failure, myopericarditis, pulmonary embolism, and acute respiratory distress syndrome represent the most serious complications of severe COVID-19. The elderly account for about 80% of deaths from COVID-19 [2]. COVID-19 comorbidities are still debated and may include hypertension, obesity, diabetes, cardiovascular disease, chronic obstructive pulmonary disease (COPD), chronic kidney disease, and malignancy [3] [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, another study of 179 patients found that patients taking PPIs were less likely to be infected by SARS-CoV-2 or to develop COVID-19. [ 111 ]…”
Section: Pre-existing Gastrointestinal and Hepatic Diseasementioning
confidence: 99%
“…A meta-analysis including more than 600.000 subjects showed that mortality changes across age categories, ranging from 9.5% (8073/ 85.358) in patients of 60-69 years old up to 29.6% (41.958/ 141.745) in those aged >80 years [14]. Table 1 and 2 summarize mortality rates extrapolated from clinical studies conducted in elderly patients with COVID-19 and factors associated with poor outcome [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Among biomarkers of infection, the increase in procalcitonin (PCT) values was associated with increased risk of hospital death in subjects > 75 years old, but not in younger ones J o u r n a l P r e -p r o o f [33].…”
Section: Clinical Presentation and Risk Of Deathmentioning
confidence: 99%